Comparison of maternal serum PlGF and sFlt-1 between pregnancies with and without fetal hemoglobin Bart's disease - Tongprasert F. (2014)
Objective: The aim of this study was to compare the levels of maternal serum placental growth factor (PlGF) and soluble fms-like tyrosine kinase-1 (sFlt-1) between pregnancies with fetal hemoglobin (Hb) Bart's disease and unaffected pregnancies. Methods: Ninety-one pregnancies at risk for fetal Hb Bart's disease scheduled for cordocentesis at 18-22weeks were recruited into the study. Maternal serum PlGF and sFlt-1 concentrations were measured before cordocentesis. Fetal blood samples were collected for thalassemia diagnosis based on fetal Hb typing using high-performance liquid chromatography. PlGF, sFlt-1, and sFlt-1/PlGF ratio were compared between the fetal Hb Bart's group and the non-Hb Bart's group (normal Hb typing or α-thalassemia-1 carrier). Results: Maternal serum concentration of PlGF was significantly higher in women with fetal Hb Bart's disease (18 cases) than those with unaffected fetuses (71 cases) (P=0.008), whereas the concentration of sFlt-1 was not significantly different (P=0.139). However, the sFlt-1/PlGF ratio was significantly lower in women with fetal Hb Bart's disease than those with unaffected fetuses (P=0.001). Conclusion: Placental growth factor may help differentiate affected from unaffected fetuses among pregnancies at risk, though further studies are needed to confirm its usefulness. In addition, preeclampsia prediction using these markers may be unreliable in pregnancies with placental dysfunction secondary to severe fetal anemia. © 2013 John Wiley & Sons, Ltd.